The Establishment Of Setback Distance For Malodour Mitigation From Palm Oil Mill - Yaacof, Nurashikin (2017)
Malaysia is the largest producer and exporter of palm oil. During the palm oil mill process, it will release an enormous amount of palm oil mill effluent which becomes a major odour problem. There are varieties of methods in managing the malodour such as biofilter, but those methods are expensive and high-maintenance. As the alternative, the setback distance method can be used as this approach is low-cost and effective. This research was carried out to verify the performance of three different setback distance methods: 1) in-field monitoring using Olfactometer, 2) the CALPUFF model and 3) the Gaussian plume model calculation. Since no research has compared the three methods, this study examined the suitability to be used in Malaysia and the effectiveness of the methods. Results show that the proper setback distances were 1.3 km by using in-field monitoring, 1.2 km by using CALPUFF model and 0.5 by using the Gaussian plume model calculation. Research shows that there a huge different in odour concentration value at the surrounding area from those methods with for 385 OU m–3 in-field monitoring, 6.1 OU m–3 for dispersion model and 81 OU m–3 for Gaussian plume model calculation. The differences was cause by the different process in running the method and also the needed data. This research can recommend a proper way to build a setback distance and setback distance value to reduce odour nuisance in the